Comparison of the Efficacy of Deep Brain Stimulation in Different Targets in Improving Gait in Parkinson's Disease: A Systematic Review and Bayesian Network Meta-Analysis - Chen, Tianyi; Lin, Fabin; Cai, Guoen (Frontiers in Human Neuroscience, 2021)
Background: Although a variety of target of deep brain stimulation(DBS) have significant effective on the Parkinson's disease (PD), it is still unclear which target of DBS has the best improvement in gait disorders in patients with PD. The purpose of this network meta-analysis is to compare the efficacy of subthalamic nucleus(STN)-DBS, internal globus pallidus(GPi)-DBS and pedunculopontine nucleus(PPN)-DBS in improving gait disorders in patients with PD. Methods: We searched the PubMed database for articles published from January 1990 to December 2020. We used various languages to search for relevant documents to reduce language bias. A Bayesian network meta-analysis and systematic review of randomized and non-randomized controlled trials were conducted to explore the effects of different DBS on target gait damage. Result: In 34 studies, 538 Parkinson's patients met the inclusion criteria. The NMA results of the effect of the DBS "on and off" on the mean change of the patients' gait in medication-off show that GPi-DBS, STN-DBS and PPN-DBS are superior to the baseline significantly (GPi-DBS: -0.79(-1.2, -0.41), STN-DBS: -0.97(-1.1, -0.81) and PPN-DBS: -0.56(-1.1, -0.021)). According to the SUCRA, ranked first is STN-DBS(SUCRA=74.15$%$), followed by GPi-DBS(SUCRA=48.30$%$) and ranked last is PPN-DBS(SUCRA=27.20$%$). The NMA results of the effect of the DBS "on and off" on the mean change of the patients' gait in med-on show that, compared with baseline, GPi-DBS and STN-DBS proved to be significantly effective (GPi-DBS: -0.53(-1.0, -0.088) and STN-DBS: -0.47(-0.66, -0.29)). GPi-DBS was rank first (SUCRA=59.00$%$), followed by STN-DBS(SUCRA=51.70$%$) and PPN-DBS(SUCRA=35.93$%$) was rank last. Conclusion: Meta-analysis results show that both STN-DBS and GPi-DBS can affect certain aspects of Parkinson's gait disorder.